1937
DOI: 10.6028/jres.018.035
|View full text |Cite
|
Sign up to set email alerts
|

The system PbO-B2O3

Abstract: The system PbO-B20 3, of interest to investigators and manufacturers of ceramic glazes and glasses, was studied by well-known methods involving quenching and petrographic examination. In addition, limits of liquid immiscibility were obtained by direct observation. Seven crystalline forms of binary compounds were found and the chemical compositions of six of these established. A number of compositions were studied also as glasses to obtain data on thermal expansion, softening behavior, and relative solubility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1939
1939
1973
1973

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…with the tetrahedral boron atoms being shared by two rings. Typical spectra are gi \'en in figure 11 for the isotopically substituted lithium compounds with the obselTed data bein g tabulated in table 13. From figure 11 it can be observed that the spectra are complex and indicative of a low symmetry and a large anion.…”
Section: Triboratesmentioning
confidence: 98%
See 1 more Smart Citation
“…with the tetrahedral boron atoms being shared by two rings. Typical spectra are gi \'en in figure 11 for the isotopically substituted lithium compounds with the obselTed data bein g tabulated in table 13. From figure 11 it can be observed that the spectra are complex and indicative of a low symmetry and a large anion.…”
Section: Triboratesmentioning
confidence: 98%
“…Comparison of the actual spectm shows marked differences in positions and relative intensities of many bands. On the basis of these 13. Absorption spectra of divalent metal tetraborates.…”
Section: Tetraborates (Xnb40 7)mentioning
confidence: 99%
“…Indicative of an approach to two-liquid immiscibility, th e curve is almost horizon tal for a chan ge in composition of n early 30 percen t. Ol'shanskii [17] investi-gated the system BaO-Si02 a bove th e liquidus, between th e temperatures of 1,800° and 2,570° C, but could find no trace of immiscible liquids. However, th e S-shaped form of the portion of th e liquids CUl've under discussion is typical of unmi~ing, or of a miscibility gap, occUl'ring completely below the liquidus…”
Section: System Bao-si02mentioning
confidence: 99%
“…Geller & Bunting (1937) reported the existence of 1 : 2, 5 : 4, 2: 1 and 4: 1 phases in this system. Bauer & Pl6tscher (1967) claimed to have found in addition 1:1 and 9:8 phases Crystalline compounds with the 5:4 and 9:8 stoichiometric ratios of metal oxide to boron oxide have not been found for other borate systems.…”
Section: Introductionmentioning
confidence: 99%